2004
DOI: 10.1107/s090904950401578x
|View full text |Cite
|
Sign up to set email alerts
|

Fischer-Tropsch synthesis: study of the promotion of Pt on the reduction property of Co/Al2O3catalysts byin situEXAFS of CoKand PtLIIIedges and XPS

Abstract: The addition of platinum metal to cobalt/alumina-based Fischer-Tropsch synthesis (FTS) catalysts increases both the reduction rate and, consequently, the density of active cobalt sites. Platinum also lowers the temperature of the two-step conversion of cobalt oxide to cobalt metal observed in temperature programmed reduction (TPR) as Co3O4 to CoO and CoO to Co0. The interaction of the alumina support with cobalt oxide ultimately determines the active site density of the catalyst surface. This interaction can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(41 citation statements)
references
References 30 publications
(42 reference statements)
3
37
0
Order By: Relevance
“…Using a standard 10 h H 2 reduction treatment of 350°C, Jacobs et al [11] showed by hydrogen chemisorption/pulse reoxidation measurements that in all cases (Pt, Ru, and Re), gains in active site densities (i.e., number of cobalt atoms exposed at the surface) were directly due to the higher extents of reduction gained by promoter addition. The three promoters, Pt, Ru and Re, have all been observed to exhibit direct contact with Co at the atomic level by EXAFS spectroscopy [12,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 97%
“…Using a standard 10 h H 2 reduction treatment of 350°C, Jacobs et al [11] showed by hydrogen chemisorption/pulse reoxidation measurements that in all cases (Pt, Ru, and Re), gains in active site densities (i.e., number of cobalt atoms exposed at the surface) were directly due to the higher extents of reduction gained by promoter addition. The three promoters, Pt, Ru and Re, have all been observed to exhibit direct contact with Co at the atomic level by EXAFS spectroscopy [12,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 97%
“…77 EXAFS studies on incipient wetness and sol gel type Pt promoted catalysts appear to indicate the existence of intimate contact betwen Pt and Co as there is no evidence for Pt-Pt bonding. 78,79 Re appears not to promote cobalt reduction until the Re itself has been reduced. 80 In all three cases the role of Pt or Re in initially reducing the cobalt is implicated in the mechanism of promotion.…”
Section: Precious Metal Promotion Effects Studied Using Nanomaterialsmentioning
confidence: 95%
“…The beamline parameters and crystal detuning procedure have been previously reported [19]. It was imperative for these binary oxide catalysts to first calculate sample thicknesses prior to visiting the synchrotron.…”
Section: Extended X-ray Absorption Fine Structure Spectroscopymentioning
confidence: 99%